Hospitalized COVID-19 Patients with Urinary Tract Infection in Iran: Candida Species Distribution and Antifungal Susceptibility Patterns - Zeinab Soleimani Shiyadeh; Shirin Farahyar; Laleh Vahedi Larijani; Justin Beardsley; Noura Nouri; Shahram Mahmoudi; Shahla Roudbar Mohammadi; Célia Fortuna Rodrigues; Maryam Roudbary (MDPI AG, 2024)
Candida species, typically part of the human skin and mucous membrane flora, can cause opportunistic fungal infections, notably urinary tract infections (UTIs), which are on the rise among hospitalized COVID-19 patients. The lack of understanding of UTIs in this population, coupled with the emergence of multidrug-resistant strains, poses significant challenges for effective treatment and further investigations. In this study, urine samples were collected from 70 COVID-19 patients with UTIs in sterile containers for microbiology examination. After microscopic observation, the isolates were identified both by phenotypic and molecular techniques such as multiplex PCR. Antifungal susceptibility testing (AFST) against fluconazole (Flu), itraconazole (Itr), and amphotericin B (AMB) was performed according to CLSI M27/S4 standard methods, with the frequency of isolates including Candida albicans (n = 20, 51.3%), Candida tropicalis (n = 15, 38.4%), Nakaseomyces glabrata (previously Candida glabrata) (n = 2, 5.1%), Pichia kudriavzevii (previously Candida krusei), and Candida parapsilosis (n = 1, 2.5%). All isolates of C. albicans, C. tropicalis, C. glabrata, and C. parapsilosis were sensitive to amphotericin B, while C. kruzei was resistant to AMB. Around 70% of C. albicans isolates were sensitive to Flu; 20% of C. tropicalis were resistant to itraconazole, while 33% were resistant to fluconazole. C. albicans and C. tropicalis were the main causes of candiduria in infected cases and both Flu and AMB showed good results in AFST in these species. Performing drug susceptibility testing for clinical isolates of Candida spp. provided guidance for appropriate management and control, and timely antifungal treatment.